Domestic dogs are mammalian reservoirs for the emerging zoonosis flea-borne spotted fever, caused by Rickettsia felis - Ng-Nguyen, Dinh (Sci Rep, 2020)
Rickettsia felis is an obligate intracellular bacterium that is being increasingly recognized as an etiological agent of human rickettsial disease globally. The agent is transmitted through the bite of an infected vector, the cat flea, Ctenocephalides felis, however there is to date, no consensus on the pathogen’s vertebrate reservoir, required for the maintenance of this agent in nature. This study for the first time, demonstrates the role of the domestic dog (Canis familiaris) as a vertebrate reservoir of R. felis. The ability of dogs to sustain prolonged periods of rickettsemia, ability to remain asymptomatically infected with normal haematological parameters and ability to act as biological vehicles for the horizontal transmission of R. felis between infected and uninfected fleas provides indication of their status as a mammalian reservoir of this emerging zoonosis.